Effect of Cattle Manure Fertilization on N, P, and K Uptake of Red Chili (Capsicum annuum L.) Grown in Alluvial Soil - Ella Saputri; Urai Suci Yulies; Vitri Indrawati (Jurnal Online Pertanian Tropik, 2025)
Red chili (Capsicum annuum L.) belongs to the Solanaceae family and can be cultivated in both lowland and highland areas. West Kalimantan has great potential for chili production on alluvial soils. This study aimed to evaluate the effect of cattle manure application on nutrient (N, P, K) uptake and yield of red chili. The experiment was conducted in Pontianak, West Kalimantan, using a Completely Randomized Design (CRD) with five treatments and five replications, resulting in 25 experimental units. Treatments consisted of P0 (control), P1 (30 tons/ha), P2 (60 tons/ha), P3 (90 tons/ha), and P4 (120 tons/ha). Results indicated that P3 (90 tons/ha) was the most effective treatment, increasing dry weight by 10.29%, N uptake by 21.42%, P uptake by 16.66%, and K uptake by 17.61%. These findings suggest that cattle manure application at 90 tons/ha significantly enhances nutrient uptake and growth of red chili in alluvial soils.